2018
DOI: 10.1109/tap.2018.2839753
|View full text |Cite
|
Sign up to set email alerts
|

Reflection, Transmission, and Absorption of Vortex Beams Propagation in an Inhomogeneous Magnetized Plasma Slab

Abstract: Based on the angular spectrum expansion and the 4x4 transfer matrix method, an investigation into the reflection, transmission, and absorption of vortex beams in an inhomogeneous magnetized plasma slab is presented. The reflected and transmitted electric fields are expressed by the inverse Fourier transform of the product of the reflected and transmitted coefficients and the angular spectrum amplitude of the incident beam. The intensity profiles, as well as the distortion of OAM states in both the reflected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This is especially true for applications in which the characteristic resonant frequencies of a substance lie within these ranges. For example, the use of terahertz and microwave vortex beams for plasma diagnostics was discussed in [88][89][90]. Another promising application is communication systems [91,92].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true for applications in which the characteristic resonant frequencies of a substance lie within these ranges. For example, the use of terahertz and microwave vortex beams for plasma diagnostics was discussed in [88][89][90]. Another promising application is communication systems [91,92].…”
Section: Discussionmentioning
confidence: 99%
“…One approach is to ignore the radial distribution of the field followed by sampling along the circle at a certain radius, see, e.g., [28,[50][51][52]]. An alternative approach, e.g., [27,[47][48][49] is to sample radial and angular distributions of the field on the whole measurement plane at the receiving end.…”
Section: Spiral Spectrum Expansion Methodsmentioning
confidence: 99%
“…They showed that the geometric properties of the sphere, e.g., the position, can be determined based on the scattering spiral spectrum data. Furthermore, the intensity distribution and OAM mode distortion of a Laguerre-Gaussian vortex beam reflected and transmitted by a non-uniform plasma plate were also examined by Li [27]. Later in 2020, Liu [28] used the physical optical algorithm to investigate the backscattering characteristics of an ideal conductive sphere and a PEC cone illuminated by a vortex beam.…”
Section: Introductionmentioning
confidence: 99%
“…e differences between the effects of three electron density profiles, with uniform, parabolic, and double exponential distributions, on the propagation properties were also compared. e angular spectrum expansion and the 4 × 4 transfer matrix method were applied by Li et al to investigate the reflection, transmission, and absorption of the vortex in an inhomogeneous and magnetized plasma slab [9]. e results proved that the parameters of the plasma have a significant impact on the magnitudes of the reflected and transmitted intensities and the distortion of orbital angular momentum states.…”
Section: Introductionmentioning
confidence: 99%